Mycobacterium Avium Complex Genitourinary Infections: Case Report and Literature Review - Sanu Rajendraprasad; Christopher Destache; David Quimby (MDPI AG, 2021)
Nontuberculous mycobacterial (NTM) genitourinary (GU) infections are relatively rare, and there is frequently a delay in diagnosis. Mycobacterium avium-intracellulare complex (MAC) cases seem to be less frequent than other NTM as a cause of these infections. In addition, there are no set treatment guidelines for these organisms in the GU tract. Given the limitations of data this review summarizes a case presentation of this infection and the literature available on the topic. Many different antimicrobial regimens and durations have been used in the published literature. While the infrequency of these infections suggests that there will not be randomized controlled trials to determine optimal therapy, our case suggests that a brief course of amikacin may play a useful role in those who cannot tolerate other antibiotics.